At Home in Exile A Memoir - Griffin, Helga M (ANU Press, 2021)
This is a story of a girl's construction of her identity, and of her family's search for a place in the world, for the Heimat that is so resonant for those of German background. We follow Helga through an adventurous childhood in Iran, whose vast open spaces her mother called 'my spiritual home'. Her engineer father worked on a grand scale, designing and laying roads and railways, and tunnelling through mountain ranges. Then came the invasions of World War II, and the family, half-German, half-Austrian, found themselves on a long voyage to Australia, designated enemy aliens. They were interned for nearly five years in the dusty Victorian countryside. On their release at the end of the War, stranded in Melbourne, they sought another home. The children were dispatched to convents, and at the Academy of Mary Immaculate, Helga found a temporary homeland, in faith. Everyday life in the Australia of the late 1940s and early 1950s is freshly seen by this feisty, loving migrant family. Through their eyes, we encounter a strange place, Australia, as if for the first time. Helga's development from a thoughtful, sensitive child to a self-possessed young woman, wrestling with her faith and with how to live a decent life, is vividly recounted.